Answer:
Explanation:
Solve for the value of :
-To find the opposite of , find the opposite of each term:
-Combine like terms:
-Take and subtract it from :
-Add on both sides:
-Divide both sides by :
So, therefore, the value of is .
9
Step 1:
2x - ( 5 - x ) = 13 + x Equation
Step 2:
2x - 5 + x = 13 + x Open the parenthises
Step 3:
3x - 5 = 13 + x Add
Step 4:
3x = 18 + x Add 5 on both sides
Step 5:
2x = 18 Subtract x on both sides
Step 6:
18 ÷ 2 Divide
x = 9
Hope This Helps :)
5.4m questions
7.0m answers